Improving The Ability of Writing News Text Through Learning Models TTW (Think Talk Write) - Susanti, Lia Dwi; Wardiah, Dessy; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The formulation of the problem in this study is: